PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL UNTUK SISWA KELAS VIII - Kemas Abdullah Azhari; KMS Badaruddin; Muslimahayati Muslimahayati (Faculty of Education and Teacher Training, State Islamic University of Sulthan Thaha Saifuddin Jambi, 2020)
This study aimed to produce a android-based learning media that is valid, practical, and observe the potential effects on learning outcomes. The type of research used in the development research method which consists of the Preliminary stage (preparation and design phase) and the Prototyping stage using formative evaluation used (Self Evalution, one to one, small group, and field test). Data collection is done using validation sheets, questionnaires, tests, and documentation. The subjects used students of class VIII of Palembang 40 Junior High School 2020/2021. 6 students were taken randomly at the One to One stage, 9 students in the Small Group stage, and 3 classes in the field test stage. The results of this study were (1) produced android-based learning media on linear equation system of two variables matter which was valid. (2) produced android-based learning media on linear equation system of two variables matter which was praktical yet. Because not all students can install it on their Smartphone. (3) The potential effect that appears at the trial stage to make students more interested and active later on student learning outcomes. seen from the average field test which reached 76.25%, this value is included in the good category